Nutritive value of elephant grass silage added with cottonseed cake in diet for sheep - Dias, Elyane Cristina; Cândido, Magno José; Furtado, Rafael; Pompeu, Roberto Claúdio; Silva, Leane (Revista Ciência Agronômica, 2019)
The objective was to evaluate the intake, nutrient digestibility and nitrogen balance in sheep fed diets containing elephant grass (Pennisetum purpureum Schum) silage containing 0; 7; 14 and 21% cottonseed cake. Twenty Morada Nova sheep were used in a completely randomized design with four treatments and five replicates. The diets were isoproteic, isoenergetic and isofibrous. There was no effect of cottonseed cake levels on nutrient intake and digestibility coefficient of ether extract. The digestibility coefficients of dry matter, organic matter, crude protein, total carbohydrates and non-fiber carbohydrates presented a linear reduction with the levels of cottonseed cake varying from, respectively, 537.97 to 421.21; 566.54 to 446.42; 595, 38 to 415.62; 544.90 to 421.84 and 697.85 to 521.03, at levels 0 and 21%. The N intake and the urinary N, in the various forms, as well as the fecal N expressed in g day-1 and g kg-0.75, were not influenced by the cottonseed cake levels in the silages. The fecal N presented a quadratic response with a minimum value of 39.09% NI when 3.20% cottonseed cake was added to elephant grass silage. Nitrogen balance showed a quadratic response with a maximum value of 6.50 g day-1; 0.79 g kg-0.75 and 35.07% NI at the levels of 3.25, 5.00 and 4.95% cottonseed cake, respectively. The inclusion of 5% cottonseed cake in elephant grass silage promotes better efficiency in the use of protein sources when aimed at using silage in the composition of a balanced diet.